A Rare Presentation of Systemic Lupus Erythematosus with Juvenile Dermatomyositis - Ashish Varma1 , Sneh Kumar2 , Rupali Salve3 , Anjali Kher4 , Jayant Vagha4 , Sachin Damke5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The systemic lupus erythematosus (SLE) is a rare type of autoimmune disease, which is associated with theinvolvement of multiple systems. It is characterized by the production of autoantibodies. Usually, it has arelapsing and remitting course. Juvenile dermatomyositis is the most prevalent chronic inflammatory muscledisease among children and adolescents with SLE. This disease predominantly involves the skin and skeletalsystem. Its most common symptoms include distinctive skin rashes and inflamed muscles. The insufficientdisposal of apoptotic cells may result in the stimulation of T cells and B cells by the antigens in the patientswith SLE. At the surface of the dying cell, fragments of cellular material develop during the cycle of celldeath. We presented the case of a 15-year-old female, who complained of erythema and generalized rashpresent on the face, markedly present over her cheek, bridge of the nose and the forehead since 7 months. Shedeveloped erythematous, scaly and crusted lesions on the scalp, back, trunk and upper limbs along with thevesiculobullous lesion of the oral mucosa. She also developed a progressive generalized muscle weaknessfor the past 3 months. To a large extent, intravenous glucocorticoids are helpful, but standardization of testsand treatment schemes are required to enhance the awareness of this rare case.